TEACHING SLOW LEARNERS IN MATHEMATICS: YUGAL REMEDIATION MODEL AS ALTERNATIVE METHOD - Yusha’u, M. A. (Sokoto Educational Review, 2012)
Considering the importance of teaching and learning of mathematics today one of the greatest challenges to a mathematics teacher is teaching mathematics to children who are slow learners. Slow learners are considered to be those children who are of limited intelligence with any or a combination of identifiable dysfunctionalities like attention deficit disorders (ADD), dyscalculia, dyslexia, dysgraphia, dyspraxia, dysnomia, hyperactivity or other related problems. Slow learners are being characterized as functioning at ability significantly below grade level and consistently scoring low on achievement tests. Most mathematics teachers have little or no consideration of the needs of slow learners in mathematics classrooms. As pan of the means to improve the achievement level of slow learners, this paper discusses the definition of slow learners, basic causes of slow learning, identifiable characteristics of slow learners and suggests the use of YUGAL as an alternative teaching method that could best be used in teaching slow learners. The paper recommends mathematics teachers to use YUGAL remediation mode! appropriately when teaching mathematics to slow learners.